Between professional success, inner exile and oblivion. The Castile and Leon women’s inspectorate in the sanctioning processes of the Spanish civil war - Sanz Simón, Carlos; Español (Historia y Memoria de la Educación, 2022)
A knowledge of the Inspectorate of Primary Education in the first third of the twentieth century is necessary if we are to know about education during this period. It is crucial that we approach this study from a gender perspective in order to make visible the biases faced by this professional body and to understand the possibilities of action of those who formed part of it. These are the premises on which this study is based. Contextualized in the current Autonomous Community of Castile and León, our aim is to analyse the punishments suffered by female primary school inspectors in this region during the period of the Civil War and the immediate repercussions that these punishments had on the careers of the protagonists. To this end, we examine professional and purification files, whose difficulties point to a prolific line of research, one subject to multiple conditioning factors as well as different interpretations. The results show how female professional inspectors suffered different punitive processes from their male counterparts, with removal from office and internal exile being two of the most common sanctions. The historical period in which they were trained, the provinces in which they worked, their political involvement and the relationships they established with significant male officials were determining factors in whether they kept their jobs after the war or were further ostracised.